2013
DOI: 10.1007/s00204-013-1101-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces unfolded protein response in vascular endothelial cells

Abstract: Chronic arsenic exposure has been linked to endothelial dysfunction and apoptosis. We investigate the involvement of unfolded protein response (UPR) signaling in the arsenic-mediated cytotoxicity of the SVEC4-10 mouse endothelial cells. The SVEC4-10 cells underwent apoptosis in response to As2O3 dose- and time-dependently, accompanied by increased accumulation of calcium, and activation of caspase-3. These phenomena were completely inhibited by α-lipoic acid (LA), which did not scavenge ROS over-production, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Recently, a role of ROS as the inducer of autophagy has been reported (Lee et al 2012). Meanwhile, our current findings were consistent with previous consensus that arsenic-induced cytotoxic effects were ROS-dependent (Weng et al 2013; Srivastava et al 2013; Kumagai and Sumi 2007). It has been demonstrated that GSH depletion was deeply involved in arsenic-induced ROS production (Yu et al 2013; Thompson and Franklin 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a role of ROS as the inducer of autophagy has been reported (Lee et al 2012). Meanwhile, our current findings were consistent with previous consensus that arsenic-induced cytotoxic effects were ROS-dependent (Weng et al 2013; Srivastava et al 2013; Kumagai and Sumi 2007). It has been demonstrated that GSH depletion was deeply involved in arsenic-induced ROS production (Yu et al 2013; Thompson and Franklin 2010).…”
Section: Discussionsupporting
confidence: 93%
“…ER stress is provoked by the accumulation of unfolded or misfolded proteins in the ER lumen as a result of an imbalance between the load and capacity of protein folding (Ron and Walter, ; Pan et al, ). Increasing evidence has also revealed a direct connection between the production of ROS and ER stress (Malhotra and Kaufman, ; Weng et al, ). Generally, when ER stress occurred, some molecules such as GRP78, ATF6 would increase significantly (Lee, ; Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…2015), or by the mitochondrial‐targeted antioxidant tiron (Weng et al. 2014). Since arsenic trioxide has been shown to increase mitochondrial ROS production possibly via an impairment of the respiratory chain (Paul et al.…”
Section: Introductionmentioning
confidence: 99%